(untitled) - Nofsinger, John R. (Upper Saddle River, 2005)
This book is the first of its kind to delve into the fascinating and important subject of the psychology affecting investments. Its unique coverage describes how investors actually behave, the reasons and causes of that behavior, why the behavior hurts their wealth, and what they can do about it. Chapter topics include overconfidence, fear of regret and seeking pride, considering the past, mental accounting, forming portfolios, representativeness and familiarity, social interaction and investing, mood and investing, and self control and decision making. anyone who wants to invest (either professionally or personally), as well as portfolio managers, fund managers, pension managers, financial advisers, brokers, financial planners, traders, financial analysts, and CPAs.
Keywords: Investments; Psychological aspects